Silicon Injection Granulomata: 67Ga Citrate Findings in Free Silicon Buttock Augmentation. (June 2016) - Strauss, Sara; Chun, Kwang; Benchekroun, Mohammed Taoudi; Akamnonu, Olisaemeka; Freeman, Leonard
Abstract : Abstract: 67 Ga citrate is frequently used in the workup of fever of unknown origin. Here, we report a case of avid 67 Ga-citrate in bilateral gluteal regions of a patient with a history of free silicon injection buttock augmentation referred for suspected diagnosis of sarcoidosis. CT findings were equivocal for inflammation/infection in the buttock region, and nuclear scintigraphy allowed for more definitive diagnosis.